ANTINOCICEPTIVE EFFECT OF AMITRAZ IN MICE AND RATS - Queirozneto, A.; Juang, S. J.; Souza, K. R.; Akamatsu, A. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
Amitraz, a formamidine insecticide and acaricide used in veterinary practice, presents side effects related to its pharmacological activity on az-adrenergic receptors. The present study was undertaken to investigate the antinociceptive effect of amitraz in rats and mice. The tail-flick test was used to determine the duration of the antinociceptive effect of the intraperitoneal tip) administration of amitraz (1 and 2 mg/kg, 10 animals per group) in male Wistar rats weighing 180-220 g. The writhing test (using 10 ml/kg of a 0.6% acetic acid solution as a painful stimulus). was performed in 140 male Swiss mice weighing 20-30 g, divided into 14 groups that received ip injections of saline, amitraz (0.5, 1.0, 1.5, 2.0 and 4.0 mg/kg), xylazine or detomidine (1.0, 1.5, 2.0 and 4.0 mg/ kg), in order to compare the effect of amitraz to that caused by xylazine and detomidine, and to investigate the participation of alpha(2)-adrenergic receptors which were blocked by idazoxan (1 mg/kg). Amitraz induced a significant antinociceptive effect in both rats and mice. This effect is blocked in mice by idazoxan.
Keywords: Amitraz; ANTINOCICEPTIVE EFFECT; ALPHA(2)-ADRENERGIC AGONISTS; IDAZOXAN; XYLAZINE; DETOMIDINE; TAIL FLICK TEST; WRITHING TEST